557 A Novel Peer-Led Anatomage-Based Teaching Programme for Medical Students. (4th May 2021) - Banjoko, A; Boylan, C; Kumar, H; McCabe, H; Morris, S
Abstract: Introduction: Anatomical knowledge is an essential part of surgical practice. However, its delivery lacks a standardised approach across medical school curricula. A student-led anatomy programme was implemented at a single institution, using near-peer teaching and Anatomage virtual dissection. This study aims to describe the methodology of this programme and determine the benefit of a near-peer taught anatomy course. Method: The programme was organised by senior medical students, utilising Anatomage virtual dissection and techniques in line with Bigg's constructive alignment. Attendees were asked to complete questionnaires with Likert scales (0-10) and open answer text to determine learners' benefit. Both quantitative and qualitative analyses are presented. Results: 73 students attended eight sessions from January to March 2020. Students reported a statistically significant (p < 0.01) increase in confidence after the sessions of 3.74±1.83. The quality and relevance of the teaching also scored highly (9.32±0.89 and 9.47±0.86 respectively). Qualitatively, students praised the "informal learning environment", the structure of the sessions, the handout provided, and the interactivity of anatomage technology. Conclusions: This study demonstrates how virtual dissection technology and near-peer teaching can derive significant benefit to undergraduate students, in line with previously published data.